Electric current stimulation of hydrogen diffusion through an amorphous palladium membrane - Prochwicz, Wojciech; Kolano, Roman; Stępień, Zdzisław (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
The work presents the results of the diffusion of hydrogen through a membrane made of amorphous palladium alloy in which one of the surfaces was modified with a layer of carbon nanotubes. We used an amorphous membrane made with a single roller spinning technique. The measurements were performed at ambient temperature. In this work, an attempt was made to study the impact of the flow of electric charge on the diffusion of hydrogen through thus modified amorphous palladium alloy membrane.
Optica Applicata, Vol. 39, 2009, nr 4, s. 799-805
Keywords: optyka; permeability; hydrogen; nanotubes; palladium alloys; membrane; metallic glasses